2017
DOI: 10.1038/s41598-017-16771-x
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Cerrena sp. laccase: preparation, thermal inactivation, and operational stability in malachite green decolorization

Abstract: Laccases are polyphenol oxidases with widespread applications in various industries. In the present study, the laccase from Cerrena sp. HYB07 was immobilized with four methods, namely entrapment in alginate, covalently binding to chitosan as well as formation of cross-linked enzyme aggregates (CLEAs) and magnetic CLEAs (M-CLEAs). The activity recovery rates of the immobilized laccases ranged from 29% to 68%. Immobilization elevated the reaction temperature optimum and reduced substrate specificity, but not nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 37 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…This result suggested that the Im-LMS exhibited a dye removal efficiency similar to that of the free LMS. The MG decolorization by laccase immobilized on various matrix was presented in the literature [ 36 , 37 ]. For example, the decolorization yields of MG by laccase immobilized on titanium oxide were 90% within 6 h [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggested that the Im-LMS exhibited a dye removal efficiency similar to that of the free LMS. The MG decolorization by laccase immobilized on various matrix was presented in the literature [ 36 , 37 ]. For example, the decolorization yields of MG by laccase immobilized on titanium oxide were 90% within 6 h [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the decolorization yields of MG by laccase immobilized on titanium oxide were 90% within 6 h [ 36 ]. The decolorization yields of MG by cross-linked laccase aggregates were 95% within 6 h [ 37 ]. Moreover, the decolorization yields of MG by coimmobilized Laccase-acetylacetone system were 95% within 48 h [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…by adsorption using chitosan beads as a support. In their study, due to stabilization of the enzyme upon immobilization, the half-life of the immobilized laccase was found to be almost twice that of the free biocatalyst [68]. By contrast, in a study by Tavares et al in 2015 [69], commercial laccase was immobilized by adsorption using multi-walled carbon nanotubes.…”
Section: Characterization Of Products Following Immobilizationmentioning
confidence: 90%
“…Immobilization of these enzymes, for example as CLEAs or combi-CLEAs is necessary in order to be cost-effective in waste water treatment. Although it is difficult to achieve the very low enzyme costs required for commercial viability in waste water treatment in general there may very well be niche opportunities in the case of emerging micropollutants that are difficult to remove by other means For example, laccase-m-CLEAs [197,198] and a combi-m-CLEA of horseradish peroxidase and glucose oxidase [199] have been used for the decolorization of recalcitritant dyes in waste water and various reactor concepts have been considered. A laccase-m-CLEA was also used for removal of pharmaceuticals from waste water [200] and an acrylamidase m-CLEA was used to catalyze the biodegradation of acrylamide in industrial waste water [201].…”
Section: Ligninolytic Enzymes and Waste Water Treatmentmentioning
confidence: 99%